MANAGEMENT MATERI DAKWAH DALAM PERKEMBANGAN MEDIA SOSIAL - ajeng wahyuni (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2019)
Indonesian society is currently experiencing changes in the context of the missionary movement. A da’i celebrity in her missionary activities has not been oriented towards the resulting impact. Research on organizing da’i's da'wah message has the purpose of knowing the organization of messages in preaching. Based on the theme raised in this study formulate a problem about how to construct da'wah messages, how to form Al Habsyi's da'wah messages. Relevant to the objectives, this study uses qualitative methods with a case study approach. Da'wah messages conveyed by cleric Al Habsyi namely mubasyaroh. Organizing messages by increasing the attention of mad’u, through nasyid, the needs of mad’u, fulfillment of the material of mad’u preaching on religious messages, describes the contents of the message of da'wah, through stories. Utilizing stories and taking actions with persuasive communication, namely by carrying out the Sunnah.